Enhancing Education on Protective Measures through Visual Arts and the STEAM Approach in First and Second-Grade Elementary School - Liakopoulou, Dimitra; Koumoutsakou, Olga; Lyras, George; Kontakiotis, George; Antonarakou, Assimina (Bulletin of the Geological Society of Greece, 2025)
This study explores how visual arts, when integrated in the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning process, could affect seismic safety education among first- and second-grade elementary students. The results of this study show that when varied methods are used in the teaching process, students are able to understand and apply protective measures more effectively. It also shows that traditional rote-based teaching is less effective than interactive, interdisciplinary learning, which seems to significantly promote students’ engagement and critical thinking. This study suggests that an expanded use of the STEAM approach in educational curricula can improve young learners’ safety awareness and preparedness for seismic events.